2004
DOI: 10.1017/s0266467404001725
|View full text |Cite
|
Sign up to set email alerts
|

General herbivore outbreak following an El Niño-related drought in a lowland Panamanian forest

Abstract: A severe outbreak of Lepidoptera followed the 1997–98 El Niño Southern Oscillation event, during which the climate in central Panama was unusually dry. The outbreak involved the larvae of at least 12 species of Lepidoptera and occurred at a seasonally dry, deciduous forest site, where extensive background data were available regarding climate, tree species and non-outbreak herbivory levels. Most Lepidoptera were associated with only one or two larval host plant species belonging to the same family, and the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 24 publications
1
74
2
Order By: Relevance
“…Our results conflict with those of a previous study conducted at PNM in 1998 which showed that wasps were relatively scarce until the end of the wet season, while flies dominated the early part of the wet season (Van Bael et al 2004). The extended dry season of 1998 due to the El Nino Southern Oscillation resulted in a massive caterpillar outbreak with large trees being almost completely defoliated (Van Bael et al 2004). Therefore, results from these two studies may be explained by differences in collections of external feeders and shelter builders or annual variability in dryseason length and its impact on decoupling caterpillar and parasitoid populations.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results conflict with those of a previous study conducted at PNM in 1998 which showed that wasps were relatively scarce until the end of the wet season, while flies dominated the early part of the wet season (Van Bael et al 2004). The extended dry season of 1998 due to the El Nino Southern Oscillation resulted in a massive caterpillar outbreak with large trees being almost completely defoliated (Van Bael et al 2004). Therefore, results from these two studies may be explained by differences in collections of external feeders and shelter builders or annual variability in dryseason length and its impact on decoupling caterpillar and parasitoid populations.…”
Section: Discussioncontrasting
confidence: 99%
“…Dominant vegetation includes tabonuco, Dacryodes excelsa Vahl (Burseraceae), which represents 35% of the forest canopy below 600 m elevation (Brown et al 1983 Tropical forests often are thought to be relatively stable. However, many tropical forests, including the LEF, are subject to frequent hurricane and drought disturbances, which alter the structure and composition of forest communities (Van Bael et al 2004, Scatena et al 2012). Prior to 1989, Puerto Rico had not experienced a major hurricane (≥ Category 3, >178 kph wind speed) for 33 years (Betsy in 1956), and a closed canopy with little understory characterized the forest.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Such long records aid greatly in identifying environmental factors responsible for population change (Morris 1964). Outbreaks are frequently triggered by drought or other host-stressing events (Mattson and Haack 1987;Van Bael et al 2004;Stige et al 2007;Schowalter 2012Schowalter , 2016. On the other hand, intolerant species may be eliminated by disturbances or require long periods for population recovery (Willig and Camilo 1991).…”
Section: Arthropod Responses To Disturbancesmentioning
confidence: 99%
“…For example, in the wet tropics, fluctuations in rainfall can have drastic effects on insect dynamics (Kirkpatrick 1957, Harvey andMallya 1995). Tropical insect populations fluctuate annually (Wolda 1978), and outbreaks do occur, though they are relatively rarely reported (Fletcher 1967, Gray 1972, Piyakarnchana 1981, Harvey and Mallya 1995, Van Bael et al 2004). …”
mentioning
confidence: 99%